The dark side of buyer–supplier relationships: A social capital perspective⋆ - Villena, Verónica H.; Revilla, Elena; Choi, Thomas Y. (Journal of Operations Management, 2011)
AbstractThe literature on supply chain management (SCM) has consistently promoted the “bright side” of collaborative buyer–supplier relationships (BSRs). Based on the social capital argument, SCM scholars have investigated how a buyer can gain access to and leverage resources through its collaborative BSRs. Our study extends this research stream by considering the “dark side” of social capital in BSRs. It evaluates how social capital in its cognitive, relational, and structural forms contributes to or impedes value creation within BSRs. Both primary survey measures and secondary objective measures have been used in data analysis. The results show the presence of both the bright side, confirming the existing literature, and the dark side, extending the literature. There is an inverted curvilinear relationship between social capital and performance: Either too little or too much social capital can hurt performance. This study confirms that building social capital in a collaborative BSR positively affects buyer performance, but that if taken to an extreme it can reduce the buyer's ability to be objective and make effective decisions as well as increase the supplier's opportunistic behavior. Our study also examines how a buyer can delay the emergence of the dark side. It opens up new research avenues in the collaborative BSR context and suggests directions for future research and practice.